Gender Analysis of the Current War Conflict in Afghanistan and the International Community's Response - Khamitova, Sayazhan; Kočí, Kateřina; Přikryl, Pavel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis explores the gender dynamics of the current conflict in Afghanistan. The main objectives of the research are to analyse the current Afghan conflict in depth, with a focus on gender aspects, and to assess the international community's response to the gender dynamics in the region. The research methodology includes qualitative analysis of interviews and reports as well as quantitative analysis of statistical data. The application of a mixed method allowed the problem to be examined from both theoretical and empirical perspectives. The findings show that the conflict in Afghanistan exacerbates traditional gender roles and increases violence against women, while the international community's efforts to address these issues are not sufficiently effective due to cultural or religious barriers. The findings underscore the need for more targeted international programmes that are culturally and gender sensitive.
Vedoucí práce: Kateřina Kočí
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses